Does the use of cochlear implants determine the reading strategies of deaf students? - Virginia González Santamaría; Ana Belén Domínguez Gutiérrez (INFAD, 2017)
Oral language determines the reading levels and language ability of deaf students. The objective of the present study was to assess both the language competence and the reading strategies used by deaf students with and without a cochlear implant (CI). In a society such as ours, where access to information and communication require high reading competency, the use of cochlear implants in deaf children plays an important role, above all, and to a greater extent, when the implant has been put in place at an early age (before 30 months). The present study reveals that the reading levels of deaf children who received cochlear implants at an early age do not differ significantly from those obtained by hearing children of the same chronological age. However, when the reading strategies used in order to reach this reading level were analysed, it was observed that deaf pupils (with or without cochlear implants) make use of the Keyword Strategy consisting in reading sentences by only processing the words with their own semantic content (nouns, verbs and adjectives) and, from there, processing what they mean without processing the functional words (prepositions, linking words and adverbs). This situation shows the difficulties which deaf pupils have with the morphological processing of language.